Effects of rainfall patterns in dry and rainy seasons on the biomass, ecostoichiometric characteristics, and NSC content of Fraxinus malacophylla seedlings - Zheng, Shaojie; Cha, Xiaofei; Dong, Qiong; Guo, Huanxian; Sun, Lijuan; Zhao, Qize; Gong, Yunqi (Frontiers in Plant Science, 2024)
With global climate change and rising temperatures, rainfall will change. The impact of global rainfall changes on ecosystems has prompted people to delve deeper into how changes in rainfall affect plant growth; Plant biomass, nutrient element content, and non-structural carbohydrate content are very sensitive to changes in precipitation. Therefore, understanding the impact of rainfall changes on seedlings is crucial. However, it is currently unclear how the seedlings of Fraxinus malacophylla Hemsl in rocky desertification areas respond to changes in rainfall. In this study, the response of biomass, nutrient accumulation, and NSC content of Fraxinus malacophylla Hemsl seedlings to different rainfall intervals and rainfall during the dry and rainy seasons was studied. Use natural rainfall duration of 5 days (T) and extended rainfall duration of 10 days(T+) as rainfall intervals; average monthly rainfall was used as the control (W), with a corresponding 40% increase in rainfall (W+) and a 40% decrease in rainfall (W-) as rainfall treatments. The research results indicate that the biomass of roots, stems, and leaves, as well as the accumulation of C, N, and P in Fraxinus malacophylla Hemsl seedlings increase with the increase of rainfall, while the soluble sugar and starch content show a pattern of first increasing and then decreasing. The biomass and nutrient accumulation of each organ showed root>leaf>stem. Except for the beginning of the dry season, prolonging the duration of rainfall in other periods inhibits the biomass accumulation of Fraxinus malacophylla Hemsl seedlings, and promotes the accumulation of C, N, and P nutrients and an increase in soluble sugar and starch content. There was a significant positive correlation (P<0.05) between the nutrient contents of C, N, and P in various organs, as well as between soluble sugar and starch content; And N: P>16, plant growth is limited by P element. These results indicate that changes in rainfall can affect the growth and development of Fraxinus malacophylla Hemsl seedlings, increasing rainfall can promote biomass and nutrient accumulation of Fraxinus malacophylla Hemsl seedlings, and prolonging rainfall intervals and reducing rainfall have inhibitory effects on them. The exploration of the adaptation of Fraxinus malacophylla Hemsl seedlings to rainfall patterns has promoted a basic understanding of the impact of rainfall changes on the growth of Fraxinus malacophylla Hemsl. This provides a theoretical basis for understanding how Fraxinus malacophylla Hemsl can grow better under rainfall changes and for future management of Fraxinus malacophylla Hemsl artificial forests in rocky desertification areas.